Updating of contents in university teaching - Gallego-Sánchez-Torija, Jorge; García-Herrero, Jesús; Bedoya-Frutos, Cesar (Advances in Building Education, 2022)
As a result of the integration of the university system in the European Higher Education Area in 2010, competences, methodology and evaluation have attracted the attention of researchers in the field of university teaching, while the contents have been relegated to a background. The present research aims to find out whether the contents that are taught respond to the changing demands of society or, otherwise, remain static and may become obsolete. The compulsory subject "Facilities Project" of the Degree in Fundamentals of Architecture at the Polytechnic University of Madrid is chosen as a case study. For this, an open survey is carried out to the students who take it in two successive years. As it is an open survey, students are offered a greater opportunity to express freely, both their answers and the reasons they have forgiving them. It is detected that they positively value much of the content and that they also value, to a lesser extent, other content negatively. Different evaluations are collected for each of the topics that make up the subject and also the reasons that, together with the suggestions, allow measures to be taken to improve the content offered. It is concluded that the contact with the opinion of the students allows obtaining a valuable point of view when keeping the contents updated.